Improvement of the technology of garden strawberry jam in combination with apple puree - Zamorska, Iryna; Zamorskyi, Volodymyr; Halahur, Yuliya; Osyka, Viktor; Belinska, Svitlana; Motuzka, Iuliia; Bozhko, Tetiiana; Krasulya, Olena; Fil, Mariia (Eastern-European Journal of Enterprise Technologies, 2019)
Strawberry jam is the most popular and valuable product of processing from strawberries, the technology of production of which involves the use of pectin solution to form the necessary jelly-like consistency, which, in turn, is accompanied by an increase in production costs and complication of manufacturing process. To solve the problem, we proposed the technology of production of strawberry jam from strawberries with the replacement of pectin solution with apple puree in the quantity of 1, 2, 3, 5, 10, 15, 20, 25, 30, 35 and 40 % of the weight of berries followed by boiling to the content of dry soluble substances of not less than 62 %, packing in a glass container with the capacity of 250 cm3, sealing, sterilization and storage at the temperature of 20±1 °C. The experiment should be repeated thrice. We studied the content of dry soluble substances, sugars, organic acids, and ascorbic acids in jams. The organoleptic indicators of jam quality were assessed by the 5-point scale. The results were analyzed by the Tukey criterion at the significance level of 5 % (p≤0.05). It is determined that by the content of dry soluble substances, jams meet the requirements of DSTU 4900, according to which mass fraction should be not lower than 62 %, of sugars – 56.2–57.2 %, titrated acids – 0.6–0.8 %, ascorbic acids – from 30.0 to 38.7 mg/100 g at its preservation at the level of 47.7–55.5 %. The study of organoleptic quality indicators showed that the addition of apple puree in the amount of 20 % and higher led to an increase in the estimate of jam consistency, which was caused by the formation of the necessary jelly-like consistency. However, the addition of puree of over 25 % resulted in a decrease in overall score due to deterioration in the appearance of jams. It was proved that 25 % of apple puree should be added in order to obtain optimum jelly-like characteristics of strawberry jam